Evaluating Smile Esthetics After Extraction and Non-Extraction Orthodontic Treatment.: A Comparative Study - BS, Raju (Journal of Neonatal Surgery, 2025)
Background: Smile esthetics is a primary concern for patients seeking orthodontic treatment. The decision to extract or not extract teeth significantly influences facial profile and smile dynamics. While both extraction and non-extraction protocols aim to achieve functional occlusion and esthetic outcomes, their comparative impact on smile esthetics remains a subject of debate. This study aims to evaluate and compare smile esthetics in patients treated with extraction and non-extraction orthodontic protocols using standardized photographic analysis. Materials and Methods: A total of 60 patients (aged 14–25 years) undergoing fixed orthodontic therapy were enrolled and divided into two groups: Group A (n=30) received extraction-based treatment (four first premolars), and Group B (n=30) received non-extraction treatment. Standardized frontal and oblique smiling photographs were taken pre- and post-treatment. Smile esthetics were assessed using parameters such as smile arc, buccal corridor width, upper lip curvature, and incisor display. A panel of three orthodontists and three laypersons independently evaluated the photographs using a visual analog scale (VAS). Statistical analysis was conducted using the independent t-test and paired t-test, with a significance level set at p<0.05. Results: Both groups showed statistically significant improvements in overall smile esthetics post-treatment (p<0.01). The mean VAS score in Group A increased from 5.8 ± 1.2 to 8.4 ± 0.9, while Group B improved from 6.1 ± 1.3 to 8.1 ± 1.0. Buccal corridor width was significantly narrower in Group A post-treatment (mean reduction of 3.5%), contributing to a more pleasing smile. However, Group B showed better preservation of the smile arc and upper lip curvature. No statistically significant difference in final esthetic ratings was observed between the two groups (p=0.32), indicating comparable esthetic outcomes. Conclusion: Both extraction and non-extraction orthodontic treatments result in significant esthetic improvement of the smile. While extraction cases tend to reduce buccal corridors, non-extraction protocols may better maintain natural smile arc and soft tissue balance. Thus, treatment planning should be individualized, focusing on skeletal, dental, and esthetic considerations